EVALUASI KUALITAS PRODUK HASIL OLAHAN DAGING SAPI PADA DEPOT DAGING SAPI SARI ECCO - Nresnandito Abrian Anggalih Hutomo; Reza Widhar Pahlevi (Bajang Institute, 2023)
The existence of competition with competitors makes the company to make products that are superior to other competitors . For this reason, there is a need for quality supervision or quality control. Quality control is needed in the supervision of the production of each company to reduce the number of defective products that can be caused then the product can be identified and known whether the product produced is in a controlled state or not. The purpose of this study was to analyze the quality of the products produced is still within the limits of quality standards , and to analyze the factors that cause the quality is not in accordance with quality standards. From the analysis using Control Charts based on X-Chart analysis, it was concluded that tofu meatballs have not met the requirements when viewed from the company standard of 5 %. From the measurement of weight (g) has a discrepancy of 39.74% or above 5%, and from the measurement of Volume has a discrepancy of 44.47% or above 5%. With the ishikawa diagram, it can be seen that the cause is caused by human factors, the environment, raw materials, production tools